Laboratory-based determinants of simulated time trial performance in cyclists - Valenzuela, P. L.; Alejo, L. B.; Montalvo-Perez, A.; Revuelta, C.; Ojanguren, D.; Lucia, A.; Barranco-Gil, D. (Biology of Sport, 2023)
Different laboratory-based variables are individually associated with cycling performance, but scarce evidence exists on which of them, when all assessed in combination,could best explain cycling performance. The present study aimed to examine the combined association between laboratory-based endurance, strength/power and body composition indicators with time trial performance in high-level cyclists. Ninety-four male cyclists were recruited (age: 20±3.5 years, maximum oxygen uptake [V O2max]: 77.7±5.4 ml· kg-1 ·min-1). Participants performed a maximal incremental cycling test for the assessment of endurance indicators (peak power output [PPO], VO2max, ventilatory threshold [VT] and respiratory compensation point [RCP]), and an incremental loading test to assess muscle strength and power-related outcomes (1-repetition maximum, mean maximal power) in the squat, lunge and hip-thrust exercises. Body composition was assessed by dual energy X-ray absorptiometry. On a separate visit, participants performed a simulated 8-minute time trial to assess cycling performance (determined as the mean power output attained). Strong-to-very-strong correlations were found between all endurance indicators and time trial performance (most r-values ranging between 0.68-0.92), whereas weakercorrelations were found forstrength/power (r-values < 0.5) or body composition (r-values < 0.7) indicators. Multivariate regression analyses revealed that VT, RCP and PPO explained together 92% of the variance in time trial performance (p < 0.001), with no significant contribution of the remaining variables. Although different endurance, strength/power and body composition individually correlate with simulated time trial performance in high-level cyclists, the former (and particularly VT, RCP and PPO) show the strongest association when all studied in combination. These findings underscore the importance of endurance capabilities (above strength/power or body composition) for maximizing time trial performance.